Research progress on exosomes from different sources in osteoarthritis and cartilage injury - Zilong Yang; Zihao Deng; Wentao Gao; Wei Zhang; Xuxuan Fan; Ke Su; Zhiqin Liu (Journal of Orthopaedic Surgery and Research)
Abstract Exosomes are nanosized membrane vesicles secreted by cells that have garnered considerable attention in the biomedical field in recent years. Osteoarthritis (OA) is a common disabling joint disease with limited therapeutic options in clinical practice. Recent studies have shown that exosomes, as crucial mediators of intercellular communication, have proven effective in treating osteoarthritis and cartilage injury in vitro and in animal models. With ongoing research, exosomes have demonstrated tremendous potential in treating and even reversing osteoarthritis and cartilage injury. They may become an emerging therapeutic strategy in the future. This review primarily discusses the composition of exosomes and explores the potential mechanisms by which exosomes from different sources influence osteoarthritis and cartilage injury in the context of ongoing advances in exosome research. Furthermore, the review highlights the progress in exosome engineering for osteoarthritis Treatment to enhance the therapeutic efficacy of exosomes.